Peran Generasi Muda dalam Memerangi Korupsi - Dea Sinta; Nurjannah, Alma; Floreta, Velma; Salsabila, Salsabila; Adelia, Rocha; Pertiwi, Niken (CV. ITTC INDONESIA, 2024)
Corruption is a serious issue that hinders the progress of a country, particularly in the economic, political, and social aspects. The younger generation plays a strategic role in the fight against corruption, as they have great potential to drive positive change in society. This article discusses the important role of the younger generation in combating corruption, including through anti-corruption education, active participation in social activities, and the use of social media as a tool for anti-corruption campaigns. This research employs a qualitative method with a library research approach. The findings show that with high awareness and access to technology, the younger generation has the potential to be effective agents of change in creating a culture of transparency and integrity. Despite facing challenges in combating deeply entrenched corruption, the younger generation can strengthen its role in the fight against corruption through heightened awareness and active involvement in various aspects of life.